2022
DOI: 10.3390/pharmaceutics14081688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Formulation Parameter-Dependent Redispersibility of API Nanoparticles from Fluid Bed Granules

Abstract: The production of nanosuspensions of poorly soluble active pharmaceutical ingredients (API) is a popular technique to counteract challenges regarding bioavailability of such active substances. A subsequent drying of the nanosuspensions is advantageous to improve the long-term stability and the further processing into solid oral dosage forms. However, associated drying operations are critical, especially with regard to nanoparticle growth, loss in redispersibility and associated compromised bioavailability. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Although the risk of agglomeration may theoretically increase with increasing compaction pressure, the threshold where the tableting process affects the redispersibility of nanocrystals seems to be formulation- and API-specific and therefore needs to be considered in drug product development. Similar API-specific characteristics for redispersibility were observed for granules loaded with nanoparticles by Wewers, Finke [ 23 ]. They reported a minimum mean nanoparticle distance to avoid agglomeration specifically for itraconazole (100 nm) and naproxen (80 nm).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although the risk of agglomeration may theoretically increase with increasing compaction pressure, the threshold where the tableting process affects the redispersibility of nanocrystals seems to be formulation- and API-specific and therefore needs to be considered in drug product development. Similar API-specific characteristics for redispersibility were observed for granules loaded with nanoparticles by Wewers, Finke [ 23 ]. They reported a minimum mean nanoparticle distance to avoid agglomeration specifically for itraconazole (100 nm) and naproxen (80 nm).…”
Section: Discussionsupporting
confidence: 74%
“…According to their explanation, water-soluble additives like mannitol can create hydrophilic bridges between the nanoparticles to prevent crystal-to-crystal contact and ultimately crystal growth. In addition, Wewers, Finke [ 23 ] showed that there is a correlation between the concentration-dependent nanoparticle distance within a solid intermediate and its nano-dispersibility. This same stabilizing concentration-dependent effect can be observed in the lyophilization processes of nanoparticles, where sugar is utilized as a so-called “cryo-protectant” to prevent agglomeration by acting as a spacer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation